A new method of distracting attention: Is it effective for pain and fear during phlebotomy in children? - Mine Aydemir Sahin; Yeliz Cigerci; Hamide Nur Cevik Ozdemir (Medicine Science)
This study examined the impact of a novel distraction approach on the mitigation of fear and pain experienced by children between the ages of 7 and 12 during phlebotomy procedures. A total of 246 children who underwent phlebotomy between January and March 2019 in the pediatric blood collection unit were included in this randomized controlled trial. The participants (n = 246) were randomized to the intervention (n = 123) and control groups (n = 123). A musical blood collection tube was used in the intervention group. The Personal Information form, the Children's Fear Scale (CFS), and the Faces Pain Scale-Revised (FPS-R) were used for the collection of the data. Fear and pain were primary and secondary outcomes, respectively. A formal approval from the ethics committee was sought in order to proceed with the study. In this study, the CONSORT checklist was used as a guide and ethical principles were followed. The pain intensity and fear level of the children in the intervention group (CFS=1.73±1.07; FPS-R= 1.65±1.33) were lower than those in the control (CFS=2.86 ± 1.07; FPS-R= 3.09±1.57). The reduction in the intervention group's pain intensity and fear level differed significantly (p=0.000 and p=0.000, respectively). The results showed that using the musical blood collection tube as a new distraction technique reduces fear and pain intensity during phlebotomy in children. The musical blood collection tube can be used by health professionals as a non-pharmacological method to reduce the pain and fear of children during blood collection. [Med-Science 2024; 13(4.000): 815-21]